## Elementary Technical Mathematics

Published by Brooks Cole

# Chapter 6 - Section 6.3 - Equations with Parentheses - Exercises - Page 242: 46

x=-9.2

#### Work Step by Step

Simplifying 12x + -13(x + 4) = 4x + -6 Reorder the terms: 12x + -13(4 + x) = 4x + -6 12x + (4 * -13 + x * -13) = 4x + -6 12x + (-52 + -13x) = 4x + -6 Reorder the terms: -52 + 12x + -13x = 4x + -6 Combine like terms: 12x + -13x = -1x -52 + -1x = 4x + -6 Reorder the terms: -52 + -1x = -6 + 4x Solving -52 + -1x = -6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -52 + -1x + -4x = -6 + 4x + -4x Combine like terms: -1x + -4x = -5x -52 + -5x = -6 + 4x + -4x Combine like terms: 4x + -4x = 0 -52 + -5x = -6 + 0 -52 + -5x = -6 Add '52' to each side of the equation. -52 + 52 + -5x = -6 + 52 Combine like terms: -52 + 52 = 0 0 + -5x = -6 + 52 -5x = -6 + 52 Combine like terms: -6 + 52 = 46 -5x = 46 Divide each side by '-5'. x = -9.2 Simplifying x = -9.2

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.